2018
DOI: 10.1186/s12993-017-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between cerebral dopamine neurotrophic factor (CDNF) 2 polymorphisms and schizophrenia susceptibility and symptoms in the Han Chinese population

Abstract: BackgroundSchizophrenia (SZ) is a complex polygenic psychiatric disorder caused in part by abnormal dopamine levels. Cerebral dopamine neurotrophic factor (CDNF) 2 is known to protect and repair the dopaminergic system. Dopamine dysfunction is one of the pathogenesis of SZ. However, the relationship between CDNF2 and SZ has not been previously investigated. We speculated that CDNF2 may be a susceptibility factor for SZ.MethodsTo address this issue, we carried out a study to investigate the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…As in our previous studies ( 3 , 12 ), family history (FH) was used to explore genetic susceptibility. Inclusion and exclusion criteria of SZ patients and healthy controls were in line with our previous studies ( 12 , 25 ). Inclusion of SZ: 1) patients with paranoid SZ according to DSM-IV; 2) PANSS ≥ 60; 3) male vs. female = 1:1; 4) Age range from 18 to 55 years old; 5) Han Chinese population.…”
Section: Methodsmentioning
confidence: 65%
See 3 more Smart Citations
“…As in our previous studies ( 3 , 12 ), family history (FH) was used to explore genetic susceptibility. Inclusion and exclusion criteria of SZ patients and healthy controls were in line with our previous studies ( 12 , 25 ). Inclusion of SZ: 1) patients with paranoid SZ according to DSM-IV; 2) PANSS ≥ 60; 3) male vs. female = 1:1; 4) Age range from 18 to 55 years old; 5) Han Chinese population.…”
Section: Methodsmentioning
confidence: 65%
“…SZ is characterized by positive symptoms, negative symptoms, disorganization of thoughts, behaviors, and cognitive deficits. Our previous studies observed the genetic basis for SZ psychopathology symptoms, such as GRIN2B was related to cognition deficit symptoms ( 12 ), and CDNF2 was related to negative symptoms ( 25 ). However, there are few studies regarding the association between SZ psychopathology symptoms and SLC1A1 ( 15 , 19 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of their biological grandparents and parents were of Chinese Han origin. HCs were from the same geographic areas; the inclusion and exclusion criteria of HCs were the same as reported in our previous studies (5,22).…”
Section: Subjectsmentioning
confidence: 99%